2016
DOI: 10.1177/0954410016662067
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility investigation of large-scale model suspended by cable-driven parallel robot in hypersonic wind tunnel test

Abstract: Cable-driven parallel robot is a special kind of robot, which is actuated by cables. It is already applied in the low speed wind tunnel to get aerodynamic measurement of aircraft model, and the aircraft pose could be adjusted by changing the cable length. Whether it can be used in hypersonic wind tunnel still needs further discussion. This paper presents the dynamics and aerodynamics analysis of a large-scale model supported by 6-DOF cable-driven parallel robot to investigate the feasibility of this special ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…2. The magnitudes of these external forces f e are, respectively, 19.041N, 32.183N, 48.327N, 60.949N, 70.043N and 75.706N, which were obtained through the wind tunnel tests 16 . Then according to the configuration shown in Fig.…”
Section: Cdpr With a Flat Moving Platformmentioning
confidence: 99%
See 1 more Smart Citation
“…2. The magnitudes of these external forces f e are, respectively, 19.041N, 32.183N, 48.327N, 60.949N, 70.043N and 75.706N, which were obtained through the wind tunnel tests 16 . Then according to the configuration shown in Fig.…”
Section: Cdpr With a Flat Moving Platformmentioning
confidence: 99%
“…Besides the above applications of CDPRs, CDPRs have also been used as a new type of suspension tool for wind tunnel tests [13][14][15] . In this type of application, it was found that the active cable-driven system can help reduce influence on the air fluent stemming caused by the suspension system, and hence the aerodynamic forces could be directly deduced from the cables tension in the wind tunnel test 16 . However, one of the drawbacks of CDPRs is the driving cables can only apply tensile forces, which means the structure of a cabled…”
mentioning
confidence: 99%
“…The WDT realized high-frequency harmonic motions using a wheel that was directly connected to a servo motor and accurately monitored force responses with in-line load cells. Wang et al 15,16 investigated the Hybrid pose/tension control based on stiffness optimization of cable-driven parallel mechanism in wind tunnel test and the feasibility of large-scale model suspended by cable-driven parallel robot in hypersonic wind tunnel test. Wang et al 17 proposed the back-stepping sliding mode robust control for a wire-driven parallel robot based on a nonlinear disturbance observer and proved the feasibility and validity of the proposed control scheme through both simulation and experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…3 The main advantage of the cable-based parallel robots are their light weight, unrestricted length of the drive cable, flexibility, large workspace, and small inertia over their rigid-link counterparts. 4 Consequently, the cablebased parallel robot is exceptionally well suited in many industrial applications, such as wind tunnel experiments, 5 medical rehabilitation, 6 astronomical observation, 7 aerial panoramic photographing, 8 and 3D printing. 9 The cablebased parallel robots, based on the number of cables (m) and the number of degrees of freedom (n), can be classified into three categories, that is, the incompletely restrained parallel robots (m < n þ 1), the completely restrained parallel robots (m ¼ n þ 1), and the redundantly restrained parallel robots (m > n þ 1).…”
Section: Introductionmentioning
confidence: 99%